2021
DOI: 10.1111/pce.14171
|View full text |Cite
|
Sign up to set email alerts
|

Plastic response to early shade avoidance cues has season‐long effect on Beta vulgaris growth and development

Abstract: Early-emerging weeds are known to negatively affect crop growth but the mechanisms by which weeds reduce crop yield are not fully understood. In a 4-year study, we evaluated the effect of duration of weed-reflected light on sugar beet (Beta vulgaris L.) growth and development. The study included an early-season weed removal series and a late-season weed addition series of treatments arranged in a randomized complete block, and the study design minimized direct resource competition. If weeds were present from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 75 publications
4
6
0
Order By: Relevance
“…The combined impact of shade avoidance and root interaction significantly impacted the number of sugar beet leaves and root length in the first 2 mo of growth, but all other measured response variables were primarily impacted by shade avoidance, with a substantially lesser effect of root interaction. The current field study substantiates results of previously performed large-pot studies that showed significant effects of shade avoidance on sugar beet yield potential (Adjesiwor et al 2021; Adjesiwor and Kniss 2020; Schambow et al 2019) and adds context, showing that the contribution of shade avoidance responses likely outweighs the impacts of resource depletion by weeds during the first 60 d of growth.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The combined impact of shade avoidance and root interaction significantly impacted the number of sugar beet leaves and root length in the first 2 mo of growth, but all other measured response variables were primarily impacted by shade avoidance, with a substantially lesser effect of root interaction. The current field study substantiates results of previously performed large-pot studies that showed significant effects of shade avoidance on sugar beet yield potential (Adjesiwor et al 2021; Adjesiwor and Kniss 2020; Schambow et al 2019) and adds context, showing that the contribution of shade avoidance responses likely outweighs the impacts of resource depletion by weeds during the first 60 d of growth.…”
Section: Resultssupporting
confidence: 90%
“…The combined impact of shade avoidance and root interaction significantly impacted the number of sugar beet leaves and root length in the first 2 mo of growth, but all other measured response variables were primarily impacted by shade avoidance, with a substantially lesser effect of root interaction. The current field study substantiates results of previously performed large-pot studies that showed significant effects of shade avoidance on sugar beet yield potential (Adjesiwor et al 2021 Substantial previous research on shade avoidance has characterized how plants adapt to the altered light environment caused by dense surrounding vegetation, and this work adds to that body of literature. With respect to its relevance to agronomic crops, most previous work has been done in crops harvested for seed, like corn and soybean.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations